Living with Urinary Incontinence: Potential Risks of Women’s Health? A Qualitative Study on the Perspectives of Female Patients Seeking Care for the First Time in a Specialized Center - Pintos-Díaz, María Zahara (Int J Environ Res Public Health, 2019)
Background: Urinary incontinence (UI) represents a complex problem which commonly affects women and influences their physical, mental, and social wellbeing. The objective of this study was to explore the experiences of a group of women with urinary incontinence. Methods: A qualitative exploratory study. Purposeful sampling was used. Recruited patients were females aged >18 years old with positive symptoms, signs of urinary incontinence, and attending a specialized urinary incontinence center for the first time. We collected data using interviews and participants’ personal letters. A thematic analysis was performed. Results: 18 women participated with a mean age of 47.32 years. Four themes emerged: (a) Experiencing uncontrolled urinary leakage, (b) Information based on beliefs and myths regarding UI, (c) Adapting to change and developing strategies, (d) The role of education. Women’s experiences were accompanied by feelings of stress and shame. A lack of information regarding UI was found, together with numerous misconceptions. Urinary incontinence triggers many changes in women. Some women may develop feelings of rejection towards their own body. Family involvement during these times is essential for education and promoting healthy sexual practices. Conclusions: This study highlights the importance of developing educational programs that focus on women’s information and education regarding triggering factors and coping strategies.